DISC1 and reelin interact to alter cognition, inhibition, and neurogenesis in a novel mouse model of schizophrenia - Mahoney, Heather L.; Bloom, Charissa A.; Justin, Hannah S.; Capraro, Bianca M.; Morris, Christopher; Gonzalez, David; Sandefur, Emily; Faulkner, John; Reiss, Samantha; Valladares, Angel; Ocampo, Angie; Carter, Bethany; et al. (Frontiers in Cellular Neuroscience, 2024)
The etiology of schizophrenia (SCZ) is multifactorial, and depending on a host of genetic and environmental factors. Two putative SCZ susceptibility genes, Disrupted-in-schizophrenia-1 (DISC1) and reelin (RELN), interact at a molecular level, suggesting that combined disruption of both may lead to an intensified SCZ phenotype. To examine this gene-gene interaction, we produced a double mutant mouse line. Mice with heterozygous RELN haploinsufficiency were crossed with mice expressing dominant-negative c-terminal truncated human DISC1 to produce offspring with both mutations (HRM/DISC1 mice). Compared to wild-type controls, these mice demonstrated impaired pre-pulse inhibition, altered cognition, and decreased activity. Diazepam failed to rescue anxiety-like behaviors, paradoxically increasing activity in HRM/DISC1 mice. At a cellular level, we found increased α1-subunit containing GABA receptors in the prefrontal cortex, and a reduction in fastspiking parvalbumin positive neurons. Maturation of adult-born neurons in the hippocampus was also altered in HRM/DISC1 mice. While there was no difference in the total number proliferating cells, more of these cells were in immature stages of development. Homozygous DISC1 mutation combined with RELN haploinsufficiency produces a complex phenotype with neuropsychiatric characteristics relevant to SCZ and related disorders, expanding our understanding of how multiple genetic susceptibility factors might interact to influence the variable presentation of these disorders.